Pemberdayaan Ekonomi Berbasis Komunitas Melalui Manajemen Bisnis Dan Inovasi Produk Olahan Singkong - Laila Wardani; Mukmin Suryatni; Muttaqillah; Wahyunadi, Hilmiati; Ni Putu Inten Nindya Paramitha (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Cassava is generally used as a snack or a substitute for rice, but it is usually processed using traditional methods because the community, particularly in rural areas, does not yet fully understand modern technology. This is reflected in a lack of creativity amongst the community, despite the existence of many cassava-based food products, as they are often unaware of the potential that can be developed from this commodity. There is a pressing need to process cassava into products with higher market value. The objective of this community service initiative is to educate the community so that untapped local potential can be optimised, particularly in ways that contribute to improving the welfare of farmers and agricultural workers. Therefore, it is necessary to develop cassava into various processed products that are long-lasting and have high economic value, such as cassava dodol, cassava sticks, cassava flour, and others, with more attractive packaging to reach a wider market network. The implementation method consists of several stages: identifying potential and issues, planning training programmes, conducting training outreach, carrying out training activities, and providing assistance to women’s groups under the auspices of the KUB Mule Angen. This activity was attended by members of the KUB Mule Angen group in Taman Sari Village, Gunung Sari Sub-district, West Lombok Regency. The results of this activity include